IMPORTANCE OF URBANIZATION OF DESERT AREAS - Haydarov Hasanjon Hakimovich (European Journal of Interdisciplinary Research and Development, 2023)
Urbanization of desert areas is a subject of growing importance in the 21st century due to rapid population growth and increasing urbanization trends worldwide. This scientific article aims to explore the significance of urban development in desert regions and its potential benefits for both the environment and human populations. The paper presents a comprehensive analysis of existing literature, highlights various methodologies utilized for desert urbanization, and provides insights into the potential outcomes and challenges faced during this process. The results demonstrate that sustainable urbanization in desert regions can contribute to ecological balance, resource management, and socio-economic development. However, careful planning, innovative technologies, and environmental considerations are crucial to ensuring successful urbanization outcomes. This article emphasizes the importance of responsible urbanization practices in desert areas to create sustainable, resilient, and thriving cities of the future.